The Use of Blended Learning in Teaching Reading - I Made Yudik Wirawan; Putu Enik Kristiani (Universitas Muhammadiyah Kalimantan Timur, 2022)
The advancement of technology, communication, and data, particularly the internet, has attracted the attention of Indonesian educators who want to use it as a source of positive learning media to support the teaching and learning process. This study aims to know the advantages of the use of Blended learning in English teaching reading skills. This literature study reviews some papers in studying the use of Blended learning and its advantages. The findings of this study showed blended learning provides many sources for the teacher and students to get the reading materials. Due to the multi-sources in blended learning, it helps the students to develop their daily reading activity. Blended Learning can make students become active learners because the students can get other additional information from the internet during online learning it is effective to make the students enjoy the learning process and do not feel bored with the monotonous learning situation. And also, the virtual class has easy access anywhere and anytime in different places at the same time and also makes it easier for teachers to create archives in digital form. The findings of this study are expected to provide teachers with information about using Blended Learning as an approach in teaching-learning activities that will benefit both students and teachers in facilitating the teaching-learning process of reading.